Donald Trump’s Political Speech: A Critical Issue “us vs them” - Rahmaniah Rahmaniah; Yuni Utami Asih; Bibit Suhatmady (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Politics is always linked to activities that have an impact on government or societal action and policies. For a variety of reasons, a speech can be a powerful tool, and any speech, particularly one intended to persuade, must be rhetorical. A persuasive speech, such as Donald Trump's, seeks to persuade the audience to accept his idea by making a reasonable claim and providing evidence to support it, because Donald Trump has the potential to be a positive force for the American economy. The purpose of this analysis is to identify how Trump uses discourse about a critical issue (the American economy) to portray a